If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3 = 27 Reorder the terms: -3 + 10x = 27 Solving -3 + 10x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 10x = 27 + 3 Combine like terms: -3 + 3 = 0 0 + 10x = 27 + 3 10x = 27 + 3 Combine like terms: 27 + 3 = 30 10x = 30 Divide each side by '10'. x = 3 Simplifying x = 3
| 2+4x^2=24 | | x^2-5x-24=24 | | k=X+273 | | k=y+273 | | 3y+4x=19 | | 13=-x+2 | | 5+2x=3x-3 | | -4x+2=-12 | | x-5x-24=0 | | x^2+5x=18 | | 2(2x-7)-6x=66-3(3x+1) | | 4w+8x-13y+3w+5x+4y= | | 3x+4y=566 | | 3ax^2+6ax-bx-2b=0 | | 7+6p-1=p-8+3p | | 15-(2w-9)=2w | | 3x^4-12x^2+2=0 | | 15m+4n-5m+10n= | | m^3-3m^2+4=0 | | 2x+3y=z+9p | | 4x^2-43x-34=0 | | 9*9*9=x | | x+(x*5)=54 | | 2x+y=3p | | 3Q^2*3Q= | | 5m^2+10m+9=0 | | 9x+3=10-3 | | -16-5x=8-9x | | 15+6y=57 | | R=143-0.65a | | 5(y-5r)+4(r+6y)=0 | | 2(4y-50)=20 |